2017
DOI: 10.1590/s1984-29612017042
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Anaplasma sp. phylogenetically related to A. phagocytophilum in a free-living bird in Brazil

Abstract: Wild animals play an important role in carrying vectors that may potentially transmit pathogens. Several reports highlighted the participation of wild animals on the Anaplasma phagocytophilum cycle, including as hosts of the agent. The aim of this study was to report the molecular detection of an agent phylogenetically related to A. phagocytophilum isolated from a wild bird in the Midwest of the state of Paraná, Brazil. Fifteen blood samples were collected from eleven different bird species in the Guarapuava r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 51 publications
1
6
0
Order By: Relevance
“…(1.67%; 7/418). Noteworthy, even though sequences similar to A. phagocytophilum have been detected in several wild animals from Brazil, negative results have been reported when a qPCR specific for this agent and based on msp-2 gene was used [6,55]. Together, these findings suggest that a putative new Anaplasma species is circulating among wild animals from Brazil.…”
Section: Discussionmentioning
confidence: 96%
“…(1.67%; 7/418). Noteworthy, even though sequences similar to A. phagocytophilum have been detected in several wild animals from Brazil, negative results have been reported when a qPCR specific for this agent and based on msp-2 gene was used [6,55]. Together, these findings suggest that a putative new Anaplasma species is circulating among wild animals from Brazil.…”
Section: Discussionmentioning
confidence: 96%
“…Several Anaplasma strains have been detected using the small-subunit rRNA (16S rRNA) which has proven to be a sensitive molecular tool to confirm the presence of these pathogens' DNA in the investigated ticks and/or animal hosts. However, 16S rRNA gene is highly conserved with few polymorphic positions, therefore, closely related species and strains cannot be distinguished (Mongruel et al 2017). On the other hand, it has been reported that the major surface protein 4 (msp 4)-that is encoded by msp4 gene-is associated with faster evolution than other nuclear genes and involved in interactions with host cells (Yang et al 2015).…”
Section: Impactsmentioning
confidence: 99%
“…However, 16S rRNA gene is highly conserved with few polymorphic positions, therefore, closely related species and strains cannot be distinguished (Mongruel et al . ). On the other hand, it has been reported that the major surface protein 4 (msp 4)‐that is encoded by msp4 gene‐is associated with faster evolution than other nuclear genes and involved in interactions with host cells (Yang et al .…”
Section: Introductionmentioning
confidence: 97%
“…Anaplasma phagocytophilum has a wide host range and complex reservoir hosts especially in rural and pastoral communities which have a shared ecosystem between humans, livestock, and wildlife [5,6]. In addition to the A. phagocytophilum livestock-human cycle, there is evidence of the bacterium circulating in wildlife vertebrates and reports show that small mammals such as mice, wood rats, and birds can harbor A. phagocytophilum without manifesting clinical signs [7][8][9][10]. Tese small mammals are reservoir hosts for many tick-borne pathogens as well as feeding hosts for various stages of tick vectors [11].…”
Section: Introductionmentioning
confidence: 99%